PENGEMBANGAN LEMBAR KERJA (LKS) BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI HIMPUNAN SISWA KELAS VII SMP N 10 MUARA BUNGO - Khairul Nisa; Buyung Buyung; Silvia Fitriani (Universitas Batanghari Jambi, 2018)
Abstract : This study aims to develop LKS based Problem Based Learning (LKS) on the set material. In addition, also see the quality of LKS developed viewed from aspects of validity, practicality and effectiveness. This type of research is research development or Research and Development (R&D). This study follows the steps of the ADDIE development model covering five stages of development: analysis, develompment, implementation and evaluation. The subject of this research is the students of class VII A SMPN 10 Muara Bungo. Research instruments on this development are questionnaires and questions. The questionnaire consisted of a validation sheet by 3 experts, materials experts, design experts, and media experts as well as individualized questionnaires, small group trials and field trials. While the instrument in the form of questions consists of a matter of pre-test and post-test. After the LKS was developed, the LKS was validated by 3 validators. The percentage of results obtained after validation is: for the material expert's assessment of 81.8% with the category